Women’s preference to apply shared decision-making in breast cancer screening: a discrete choice experiment - Montserrat Rué; Misericòrdia Carles-Lavila; Maria José Pérez-Lacasta; María José Hernández-Leal; Núria Codern-Bové; Carmen Vidal-Lancis; Angels Cardona-Cardona; Carles Forné (BMJ Open, 2022)
Objective To analyse women’s stated preferences for establishing the relative importance of each attribute of shared decision-making (SDM) and their willingness to pay (WTP) for more participatory care in breast cancer screening programmes (BCSP).Design A discrete choice experiment was designed with 12 questions (choice tasks). It included three attributes: ‘How the information is obtained’, regarding benefits and harms; whether there is a ‘Dialogue for scheduled mammography’ between the healthcare professional and the woman; and, ‘Who makes the decision’, regarding participation in BCSP. Data were obtained using a survey that included 12 choice tasks, 1 question on WTP and 7 socioeconomic-related questions. The analysis was performed using conditional mixed-effect logit regression and stratification according to WTP.Setting Data collection related to BCSP was conducted between June and November 2021 in Catalonia, Spain.Participants Sixty-five women aged between 50 and 60.Main outcome measures Women’s perceived utility of each attribute, trade-off on these attributes and WTP for SDM in BCSP.Result The only significant attribute was ‘Who makes the decision’. The decision made alone (coefficient=2.879; 95% CI=2.297 to 3.461) and the decision made together with a healthcare professional (2.375; 95% CI=1.573 to 3.177) were the options preferred by women. The former contributes 21% more utility than the latter. Moreover, 52.3% of the women stated a WTP of €10 or more for SDM. Women’s preferences regarding attributes did not influence their WTP.Conclusions The participant women refused a current paternalistic model and preferred either SDM or informed decision-making in BCSP.